Pollen cryo-preservation for hybrid seed production in hot pepper - RAKESH C. MATHAD; S. B. PATIL; G. Y. LOKESH; B. A. SAVEGOWDA (Seed Research, 2026)
Hot Pepper is one of the important vegetable crops of Asia. In hot pepper, seed production is mainly done using cytoplasm male sterile lines. For seed production, the male line is grown in a centralized facility and male buds are distributed to growers for pollen extraction and crossing of female buds. An effort was made to preserve pollen from these male buds under refrigeration and cryo- preservation, which can be used to directly supply pollen, instead of buds, to longer distances. The pollen from these male lines were harvested and stored in normal room temperature (25°C-Control), in deep refrigeration (-20°C) and in liquid Nitrogen (-196°C). The pollen lost viability after 3 days and failed to produce seeds when stored under room temperature and after 6 days in deep refrigeration. In case of cryo-preservation, the pollen could be stored up to 47 days and produced seeds up to 48 days. The pollen cryo-preservation helps in reducing cost of seed production and ensures germplasm security.